Ensemble theatre making : a practical guide - Bonczek, Rose Burnett, 1958- (Routledge, 2013)
"Ensemble Theatre Making: A Practical Guide is the first comprehensive diagnostic handbook for building, caring for and maintaining ensemble. Successful ensembles don't happen by chance: they can be created, nurtured and maintained through specific actions taken by ensemble leaders and members. Ensemble Theatre Making provides a thorough step-by-step process to consistently achieve the collaborative dynamic that leads to the group trust, commitment and sacrifice necessary for the success of a common goal. Through planning and preparation, investigating the essential building blocks of ensemble, identifying ensemble behaviours and techniques of responding to those behaviours, Ensemble Theatre Making gives tools, techniques and recipes for bringing ensemble from the realm of luck into a grounded practice. This conversational, straight-forward guide gives clarity and practical guidance to the sometimes mystifying questions of what creates ensemble bonds, how to fix them when they start to break, and how to strengthen and protect them"--